Diethylamino‐fluorographene: A 2D material with broadband and efficient optical limiting performance (from 500 to 1800 nm) with very large nonlinear optical response. Issue 4 (21st August 2020) - Papadakis, Ioannis; Stathis, Aristeidis; Bourlinos, Athanasios B.; Couris, Stelios
Abstract: The present work reports on the broadband optical limiting performance and the enhancement of the nonlinear optical (NLO) response of a diethylamino‐modified fluorographene compared to pristine fluorographene and other modified fluorographenes. The present modified fluorographene was found exhibiting very efficient and broadband optical limiting action, for optical radiations extended from the visible (i.e., 500 nm) and up to near infrared (i.e., 1.8 μm). Its optical limiting threshold was found to be better that 0.045 J cm −2 making it a very promising material for optical limiting applications. In addition, the functionalization of fluorographene by the diethylamino ligand resulted in switching on the NLO response of fluorographene, attaining a third‐order nonlinear susceptibility χ (3) of the order of 10 −9 esu under ns, visible and infrared laser excitation. The present work demonstrates the efficiency and the new horizons opened by suitable chemical functionalization of fluorographene, towards the tailoring of its nonlinear optical response and optical power limiting action, towards several applications in photonics and optoelectronics and for the preparation of materials with custom made properties. Abstract : Diethylamino fluorographene is synthesized by partial nucleophilic substitution of fluorographene by lithium diethylamide LiN(C2 H5 )2 . The functionalization of fluorographene results in switching ON its nonlinear optical response, under ns visible and infrared laser excitation. The diethylamino fluorographene exhibits efficient and broadband optical limiting action, up to 1.8 μm. The efficient tunability of the nonlinear optical properties exploiting fluorographene's chemistry is highlighted.